2008
DOI: 10.1002/ijc.23314
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tumor activity of an anti‐endoglin monoclonal antibody is enhanced in immunocompetent mice

Abstract: In the present study, we investigated the mechanisms by which anti-endoglin (EDG; CD105) monoclonal antibodies (mAbs) suppress angiogenesis and tumor growth. Antihuman EDG mAb SN6j specifically bound to murine endothelial cells and was internalized into the cells in vitro. SN6j effectively suppressed angiogenesis in mice in the Matrigel plug assay. We found that SN6j is more effective for tumor suppression in immunocompetent mice than in SCID mice. We hypothesized that T cell immunity is important for effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 31 publications
(36 reference statements)
2
66
1
Order By: Relevance
“…In this regard, there are several reported approaches using experimental animal models (55,117,156,164,165). Among these, the approach of using naked anti-endoglin monoclonal antibodies as a tumor vascular targeting agent is clinically relevant.…”
Section: Endoglin and Tumor Angiogenesismentioning
confidence: 99%
“…In this regard, there are several reported approaches using experimental animal models (55,117,156,164,165). Among these, the approach of using naked anti-endoglin monoclonal antibodies as a tumor vascular targeting agent is clinically relevant.…”
Section: Endoglin and Tumor Angiogenesismentioning
confidence: 99%
“…Endoglin antibodies have also been previously reported to induce receptor internalization and presumed to become degraded through an unknown mechanism (31,32). As part of our ongoing investigation on the anti-angiogenic properties of TRC105, we tested the functional role of the tyrosine endocytic motif in TRC105-induced endoglin internalization.…”
mentioning
confidence: 99%
“…On one hand, this could be related to the tumor grading or staging, as an increase in MVD was demonstrated by using CD105 during progressive stages of colorectal carcinogenesis [21] . On the other hand, reduced endoglin expression could also be caused by a decreased tumor vascularization in endoglin haploinsufficiency cases [22] . There are also differences in reactivity to endothelial cells depending on tumor localization [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, reduced endoglin expression could also be caused by a decreased tumor vascularization in endoglin haploinsufficiency cases [22] . There are also differences in reactivity to endothelial cells depending on tumor localization [22][23][24] . However, in colorectal cancer, other studies showed that, with cancer progression, endoglin signaling was lost in most of the epithelial cancer cells which became refractory to the TGF-β growth inhibiting properties [25][26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%